A Rare Case of Pneumoureter: Emphysematous Pyelitis versus Emphysematous Pyelonephritis - Rudresh Hiremath; Mahesh; Krishna Prasanthi Padala; Kumar Swamy; Aruna Pailoor (Journal of Clinical and Diagnostic Research, 2015)
Emphysematous pyelitis is a rare benign entity which is defined as isolated gas production in the pelvicalyceal system, ureters or in the urinary bladder as a consequence of acute bacterial renal infection. In this case report we present a case with no prior medical history of diabetes or urinary obstruction who presented with uncontrolled hyperglycaemia for the first time associated with emphysematous pyelonephritis. Further, the imaging differences between emphysematous pyelonephritis (EPN) and emphysematous pyelitis (EP) has been discussed along with the approach and their management.